Relations of phenometrical indices of apple fruits with weather variation in the assortment of varieties of an apple gene bank - Lakatos, L.; Szabó, T.; Szabó, Z.; Soltész, M.; Sun, Z.; Nyéki, J. (International Journal of Horticultural Science, 2012)
The purpose of phenometry is to examine the measurable parameters of the plants in order to follow up the consequences of weather processes. We should fi nd the reasons, why the diameter of fruits grows larger in one season and smaller in the next. Variation may occur as a response to insuffi cient provision of water or nutrients, but also because of pathological effects and of extremely high or low temperatures, moreover, of extraordinary heavy fruit load. There are phenometrical characteristics, which consider the fi nal consequences (density of fl owers, fruits set, drop of fruits), whereas other parameters could be followed up (size, length and width of fruits) as the dynamic components of growth. The quantitative parameters of growth are functionally related to each other, where the weather conditions, soil humidity and nutrients are on the input side, thus it is possible to model the growth of fruits as a function of the environment. Initially, the relations between the main weather variables and the phenometrical data have to be cleared. In the present study, the interactions between the mentioned phenomena are presented and numerically defi ned.